Formation of schoolchildren’s healthy life style culture as one of key problems of modern comprehensive educational establishment - Davydova, T.M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose : optimization of educational-teaching process in modern comprehensive educational establishment in context of pupils’ health protection. Material: in experiment 1012 pupils (of age from 11 to 15 years old), 532 students of higher educational establishments, 176 teachers, 34 methodologists and representatives of educational establishments’ administrations participated. Results: positive influence of schoolchildren’s healthy life style on general health condition has been determined. Model of formation of adolescents’ health culture, which consists of four sub-systems: health protection technologies; health related technologies; technologies of teaching to healthy life style; formation of personalities’ qualities, facilitating health strengthening, has been offered. It has been found that the presented model orients pupils on formation of positive, firm, individual picture of health as the necessary condition of their viability. Conclusions: it has been established that formation of positive motivation for healthy life style is connected with demand in reducing of secondary education system to modern conditions of renewed content of education, forms and methods of work in comprehensive educational establishments.